Imposex in Crassilabrum crassilabrum (Neogastropoda: Muricidae) in the Peruvian central coast - Rivas, Rolf (2017)
The imposex is a phenomenon that consists in the development of masculine sexual characteristics on the reproductive system of the gastropod female snails by organotin compounds (OTs), like tributyl tin (TBT). In the present study, the imposex was evaluated in Crassilabrum crassilabrum Sowerby, 1834 (Neogastropoda: Muricidae) from the central coast of Peru, for which individuals were collected from the intertidal zone of Pucusana and Ancon, Lima. Biometric measurements were taken and the rates of imposex were calculated. The percentage of imposex in Ancon was of 98% and in Pucusana of 100%. The index of relative length of the penis (RPLI) was 52.3% and 44.5% for Pucusana and Ancon, respectively. A significant relationship was found between the length of the conchilla and the length of the penis in males on both beaches, but not in females. Crassilabrum crassilabrum is a mollusk with application to be used as a bioindicator of OT components in the central coast of Peru and in the South American Pacific.